Alginate-based 3D cell culture technique to evaluate the half-maximal inhibitory concentration: an in vitro model of anticancer drug study for anaplastic thyroid carcinoma - Hilda Samimi (BMC, 2021)
Abstract Background Three-dimensional (3D) cell culture methods are identified for simulating the biological microenvironment and demonstrating more similarity to in vivo circumstances. Anaplastic thyroid carcinoma (ATC) is a lethal endocrine malignancy. Despite different treatment approaches, no improvement in the survival rate of the patients has been shown. In this study, we used the 3D in vitro ATC model to investigate the cytotoxic effect of BI-847325 anticancer drug in two-dimensional (2D)- and 3D- cultured cells. Methods Human ATC cell lines, C643 and SW1736, were cultured in one percentage (w/v) sodium alginate. Spheroids were incubated in medium for one week. The reproducibility of the fabrication of alginate beads was evaluated. Encapsulation of the cells in alginate was examined by DAPI (4′,6-diamidino-2-phenylindole) staining. Survival of alginate-encapsulated cells was evaluated by CFSE (5,6-Carboxyfluorescein N-hydroxysuccinimidyl ester) staining. The population doubling times of C643 and SW1736 cell lines cultured in 2D monolayer as well as in 3D system were calculated. The cytotoxic effect of BI-847325 on 2D- and 3D- cultured cell lines was assessed for 24–72 h by MTT [3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide] assay. Finally, the 3D culture results were compared with the 2D culture method. Results The half-maximal inhibitory concentration (IC50) values of BI-847325 were higher in 3D culture compared to 2D culture. The cytotoxicity data indicated that 3D in vitro models were more resistant to chemotherapy agents. Conclusions The findings of this study are beneficial for developing in vitro ATC 3D models to analyze the efficacy of different chemotherapy drugs and formulations.